The Chinese adaptation of turnover intention scale in early childhood pre-service teachers - Mingxing, Shao; Razali, Fazilah; Muhamad, Mohd Mokhtar; Nasiruddin, Nasnoor Juzaily Mohd; Xinchong, Sha; Wenling, Li (Institute of Advanced Engineering and Science, 2025)
The issue of teacher turnover is a global concern, with particularly devastating impacts on early childhood education. Turnover intention (TI) is the most powerful predictor of actual turnover behavior, making early identification of TI crucial for reducing attrition among early childhood preservice teachers (PSTs). Despite this, no measurement tool exists in China to assess the TI of early childhood PSTs. This study aimed to provide a Chinese version of turnover intention scale for student teachers (TIS-ST) and evaluate its psychometric properties for assessing the TI of Chinese early childhood PSTs. A stratified random sampling method was used to select a sample of 537 early childhood PSTs. The psychometric properties of the Chinese version of TIS-ST were assessed through construct validity, measurement invariance, convergent validity, internal consistency reliability, item analysis, and composite reliability analyses. The results demonstrated that the Chinese version of TIS-ST has adequate validity, reliability, and measurement invariance across age. The Chinese version of TIS-ST can facilitate the dynamic identification and understanding of Chinese early childhood PSTs’ TI across different ages and can lead to targeted interventions that address the root causes of attrition among early childhood PSTs. This can ultimately result in more stable and effective early childhood education systems.